2022
DOI: 10.1007/s11816-022-00767-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic insights in pearl millet breeding in the genomic era: challenges and prospects

Abstract: Pearl millet, a vital staple food and an important cereal, is emerging as crop having various end-uses as feed, food as well as fodder. Advancement in high-throughput sequencing technology has boosted up pearl millet genomic research in past few years. The available draft genome of pearl millet providing an insight into the advancement of several breeding lines. Comparative and functional genomics have untangled several loci and genes regulating adaptive and agronomic traits in pearl millet. Additionally, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 147 publications
0
5
0
Order By: Relevance
“…Pearl millet is a staple crop of arid and semi-arid tropics and is known for its unique ability to tolerate abiotic stress. Various studies used a genomic approach to identify genes and pathways related to abiotic stress in pearl millet [ 21 , 22 , 23 , 24 , 25 , 26 ]. However, none of the studies performed coexpression analysis to discover genes that regulate abiotic-stress-related traits.…”
Section: Discussionmentioning
confidence: 99%
“…Pearl millet is a staple crop of arid and semi-arid tropics and is known for its unique ability to tolerate abiotic stress. Various studies used a genomic approach to identify genes and pathways related to abiotic stress in pearl millet [ 21 , 22 , 23 , 24 , 25 , 26 ]. However, none of the studies performed coexpression analysis to discover genes that regulate abiotic-stress-related traits.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative and functional genomics have untangled several loci and genes that regulate adaptive and agronomic traits in pearl millet. The use of high‐throughput sequencing technology has boosted pearl millet genomic research, providing insights into its genetic and genomic characteristics (Singh and Nara, 2022). Combined studies of genomics and phenomics in pearl millet have demonstrated achievements in recent years.…”
Section: Integrating Phenomics and Genomicsmentioning
confidence: 99%
“…Pearl millet is a staple crop of arid and semi-arid tropics and is known for its unique ability to tolerate abiotic stress. Various studies used a genomic approach to identify genes and pathways related to abiotic stress in pearl millet (20)(21)(22)(23)(24)(25). But none of the studies performed a coexpression analysis to discover genes that regulate abiotic stress-related traits.…”
Section: Endocytosismentioning
confidence: 99%